2016
DOI: 10.7554/elife.13662
|View full text |Cite
|
Sign up to set email alerts
|

Structural mechanism of ligand activation in human calcium-sensing receptor

Abstract: Human calcium-sensing receptor (CaSR) is a G-protein-coupled receptor (GPCR) that maintains extracellular Ca2+ homeostasis through the regulation of parathyroid hormone secretion. It functions as a disulfide-tethered homodimer composed of three main domains, the Venus Flytrap module, cysteine-rich domain, and seven-helix transmembrane region. Here, we present the crystal structures of the entire extracellular domain of CaSR in the resting and active conformations. We provide direct evidence that L-amino acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
330
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(360 citation statements)
references
References 83 publications
(138 reference statements)
27
330
2
1
Order By: Relevance
“…Mutagenesis studies have verified the importance of this specific residue in L-␣-amino acid-mediated activation/binding of mGluR3, CaSR, and the goldfish GPRC6A ortholog 5.24 (32)(33)(34). CaSR is the closest mammalian homolog of GPRC6A, and because crystal structures of CaSR verify that Glu-297 is located in the orthosteric binding site (35,36), it is reasonable to assume that Asp-303 is also found in the orthosteric binding site of GPRC6A, although no structural information is yet available for this receptor. In the current study, the aspartic acid was thus substituted with alanine (D303A) to impair the agonist-binding site in GPRC6A.…”
Section: Gprc6a Displays Constitutive Internalizationmentioning
confidence: 95%
“…Mutagenesis studies have verified the importance of this specific residue in L-␣-amino acid-mediated activation/binding of mGluR3, CaSR, and the goldfish GPRC6A ortholog 5.24 (32)(33)(34). CaSR is the closest mammalian homolog of GPRC6A, and because crystal structures of CaSR verify that Glu-297 is located in the orthosteric binding site (35,36), it is reasonable to assume that Asp-303 is also found in the orthosteric binding site of GPRC6A, although no structural information is yet available for this receptor. In the current study, the aspartic acid was thus substituted with alanine (D303A) to impair the agonist-binding site in GPRC6A.…”
Section: Gprc6a Displays Constitutive Internalizationmentioning
confidence: 95%
“…Despite the recent technical advances, a missing piece of the GPCR signaling puzzle is crystal structure information of a heteromeric GPCR complex. The explosion of available crystal structures of GPCRs has transformed drug design strategies for the GPCR monomer model, and although crystal structures of homodimers (66)(67) and homo-oligomers (68) have been identified, heteromeric structures would provide unprecedented information, not only on interfaces, but unique heteromer-specific targeting sites for structure-based drug discovery. With the generation of antibodies that target GPCR heteromers and the use of nanobodies in GPCR research (69)(70)(71)(72)(73)(74)(75)(76), there is a real technical possibility of creating tools to aid stabilisation of such structures for crystallization.…”
Section: Specific Activation Of Gpcr Heteromersmentioning
confidence: 99%
“…In addition to its regulation by Ca 2+ ions, the CaSR also responds promiscuously to L-amino acids of various classes (Conigrave et al, 2000b), and one of the most potent, L-Trp, has been shown recently to bind in the receptor's VFT domain ligand-binding groove (Geng et al, 2016; see below). This behavior resembles that of several class C GPCRs (Conigrave and Hampson, 2006, 2010) and supports macronutrient sensing in various tissues including the gastrointestinal tract (review: Conigrave and Brown, 2006).…”
Section: The Presentmentioning
confidence: 99%
“…It is interesting to speculate that the “inactive” form of the receptor, which is promoted under conditions of low Ca 2+ and high phosphate concentrations (Geng et al, 2016) might preferentially couple to G s in the parathyroid.…”
Section: Recent Developments and The Futurementioning
confidence: 99%